Contextual influences on chronic illness: A multi-level analysis in the twin cities of Ramallah and Al Bireh in the occupied Palestinian Territory - Alkhatib, Ahmad M.; Olsen, Jonathan R.; Mitchell, Richard (Health & place, 2021)
The features of the urban environment can support human health as well as harm it, but less is known about such influences in the context of middle eastern countries. The association between green space and the political classifications of the urban environment and the risk of chronic illness was investigated in a novel setting, the twin cities of Ramallah and Albireh in the occupied Palestinian territory. We used a generalised multi-level regression analysis to link the 2017 census data with Geographic Information System data. We modelled individuals at level one (n = 54693) and areas of residence at level two (n = 228), adjusting for individual demographic and socio-economic characteristics. The proportions of ‘mixed’ trees in residential areas had a significant inverse association with the risk of chronic illness. On the political dimension, only living in a refugee camp had a significant positive association with chronic illness; however, this was largely explained and rendered non-significant when green space variables were entered into the models. Our ability to differentiate between several types of green space was important, as findings demonstrated that not all types were associated with reduced risk of chronic illness. Our results from a middle eastern setting add to the largely Western existing evidence, that trees in urban settings are important and beneficial to human health. Researchers and policymakers should pay more attention to the health consequences of refugee camps but also the role of trees in benefiting individuals' health in such a disadvantaged context. •The study explored the urban political and environmental impacts on health in the Palestinian context.•Living in a refugee camp is positively associated with the risk of chronic illness, over and above individual characteristics.•Residential areas mixed trees are inversely associated with chronic illness, and explained the association with refugee camps.•Not all types of green space are associated with a reduced risk of chronic illness.